In Search of Belonging : Latinas, Media, and Citizenship - Báez, Jillian M., 1981- (Latinos in Chicago and the Midwest., 2018)
In Search of Belonging explores the ways Latina/o audiences in general, and women in particular, makes sense of and engage both mainstream and Spanish-language media. Jillian M. Báez's eye-opening ethnographic analysis draws on the experiences of a diverse group of Latinas in Chicago. In-depth interviews reveal Latinas viewing media images through a lens of citizenship. These women search for nothing less than recognition--and belonging --through representations of Latinas in films, advertising, telenovelas, and TV shows like Ugly Betty and Modern Family. Báez's personal interactions and research merge to create a fascinating portrait, one that privileges the perspectives of the women themselves as they consume media in complex, unpredictable ways. Innovative and informed by a wealth of new evidence, In Search of Belonging answers important questions about the ways Latinas perform citizenship in today's America.